KONSTRUKSI SELF DALAM EKSPRESI BAHASA GENDER: Kajian Harmoni Sosial dalam Perspektif Hermeneutika - Abdul Syukur Ibrahim; Lilik Wahyuni (Kajian Linguistik dan Sastra, 2013)
The gain of social status, level of education, and economic power by women has altered interactional strategies between men and women. To understand the fundamental concept of I and you both men and women negotiate between self and others. The purpose of this research is to investigate the construction of self in the expressions used by men and women which includes (1) the creation of harmonious self in the expressions of men and women (2) the strategies of defining harmonious situation in the language used by both gender. This study employs the theory of impression management as part of Goffman’s dramaturgical theory of symbolic interactionism. The findings show that (1) the creation of self in the language used by both gender is realized in linguistic and pragmatic forms, (2) the strategies of defining harmonious situation are conducted by women through the validity of self-concept, demonstration of group membership, social distance, and physical stigma.